To the Problem of Developing the Concept of Organising Social and Psychological-Pedagogical Work with Adolescents on the Internet - N.V. Bogdanovich; V.V. Delibalt (Психология и право)
Modern childhood and adulthood take place in a new social situation of development. The rapid development of digital technologies and the banalisation of the Internet in the practice of everyday life of children and adolescents provide not only new opportunities for self-realisation, but also confront new threats and risks in the digital environment. Such socially significant problems as cyberbullying, online sexual grooming, Internet addiction and other manifestations pose complex tasks for professionals to build work with clients not only offline but also online. In this regard, it is necessary to comprehend new aspects of professional activity related to the need to provide assistance in the Internet environment. The article presents the concept of organisation of social and psychological-pedagogical work with adolescents in the Internet, based on the empirically verified author’s model of competences of a specialist in working with online risks and resources and developed on the basis of the scheme of activities proposed by U. Engeström. Engeström. Based on the typology of online risks, the aim and objectives, preventive orientation of the activity are substantiated, and the organisational aspects of such work are described.